Patterns of Religious Development for Students at Madrasah Aliyah - Nst, Sehat Sentosa; Zulfamanna, Zulfamanna; Suprizen, Suprizen (STIT Ahlussunnah Bukittinggi, 2025)
Religious guidance leads to patterns of guidance such as prayer and morals. Not all of the guidance programs carried out are running as they should in accordance with the objectives of religious guidance in Madrasah Aliyah. Ideally, the religious guidance and training received by students should make them understand and obedient in performing prayers, reciting the Quran, memorizing, and being serious in their studies, as well as having good character. In reality, there are still many students who do not perform their prayers, pretending to be sick even though they are able to pray. This study aims to describe the patterns of prayer and moral character development among students at Madrasah Aliyah. This study uses a qualitative method with field research as the type of research. The data sources used are primary and secondary data sources. The data collection techniques are interviews, observation, and documentation study. The data analysis techniques are data reduction, data presentation, and conclusion drawing. The findings of this study show that the pattern of student worship guidance is divided into two methods. First, the individual method, which is how students are taught to be responsible for themselves, including in performing prayers even when they are not in the Madrasah Aliyah environment. The second method is group work, which teaches students to be responsible to the group. Students are accustomed to working in groups and being responsible for their group. The groups are divided into two types: large groups and small groups. Meanwhile, the pattern of character building for students refers to the 10 characters of Asmaul Husna, with an emphasis on role modeling.